Analisis #DanceChallenge terhadap Popularitas Grup K-Pop Stray Kids pada Kalangan Generasi Z di Jakarta - Nadine, Gabriela; Junaidi, Ahmad (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
Social media has become one of the most widely used platforms for doing business. Many businesses promote their goods/services through content strategy marketing through social media. One of the most widely used social media is TikTok, with the most users being young people, generation Z. The purpose of this study is to find out the benefits of content marketing in increasing popularity and how content marketing can increase popularity. The purpose of this study is to determine the benefits of content marketing in increasing popularity and how the influence of TikTok dance challenge content in increasing the popularity of K-Pop group Stray Kids among Generation Z in Jakarta. The theories used are marketing communication theory, digital marketing (content marketing), new media theory (social media), and popularity. The approach used in this research is a combination method that combines a quantitative approach with a qualitative approach with the aim of measuring and describing the benefits of content marketing in influencing popularity. This study found the influence of the TikTok Dance Challenge Content variable on the Stray Kids Popularity variable on Generation Z subjects in Jakarta, as well as the importance of content in marketing activities. Media sosial telah menjadi salah satu platform yang paling banyak digunakan untuk berbisnis. Banyak pebisnis mempromosikan barang/jasa mereka melalui pemasaran strategi konten (content strategy marketing) melalui media sosial. Salah satu media sosial yang paling banyak digunakan adalah TikTok dengan pengguna terbanyak adalah kalangan anak muda, generasi Z. Tujuan penelitian ini adalah untuk mengetahui manfaat content marketing dalam meningkatkan popularitas dan bagaimana pengaruh konten dance challenge TikTok dalam meningkatkan popularitas grup K-Pop Stray Kids pada Kalangan Generasi Z di Jakarta. Teori yang dipakai adalah teori komunikasi pemasaran, digital marketing (content marketing), teori new media (media sosial) dan popularitas. Pendekatan yang digunakan dalam penelitian ini adalah metode kombinasi yang menggabungkan pendekatan kuantitatif dengan pendekatan kualitatif dengan tujuan untuk mengukur dan mendeskripsikan manfaat content marketing dalam mempengaruhi popularitas. Penelitian ini menemukan adanya pengaruh dari variabel Konten Dance Challenge TikTok terhadap variabel Popularitas Stray Kids pada subjek Generasi Z di Jakarta, serta pentingnya konten dalam kegiatan pemasaran.